Frequency of Anemia in Patients with Heart Failure Admitted to Cardiology Unit of Tertiary Care Hospital - Jamil Ur Rahman; Saghir, Tahir; Zaman, Shahid; Idrees, Muhammad; Shakil, Muhammad; Zada, Shakir (Indus Journal of Bioscience Research, 2025)
Background: Anemia is a common but often underdiagnosed comorbidity in patients with heart failure (HF), contributing to increased morbidity, hospitalizations, and reduced quality of life. Objective: This study aimed to determine the frequency of anemia among HF patients admitted to a tertiary care cardiology unit and explore associated clinical factors. Methods: This cross-sectional study was conducted at the Department of Cardiology, NICVD, Karachi, from February to May 2024. A total of 191 patients aged 40–80 years with a confirmed diagnosis of HF were enrolled using non-probability consecutive sampling. Patients with chronic kidney disease, blood dyscrasias, recent transfusions, malignancy, or iron supplementation were excluded. Hemoglobin levels were assessed to determine anemia status.  Results: Among 191 patients, 89 (46.6%) were found to have anemia. Anemia was significantly more common in patients aged ≥60 years (p = 0.01), with longer disease duration (p = 0.02), BMI